A redescription of Moina australiensis Sars, 1896 (Cladocera: Moinidae) with short notes on Australian moinids - Neretina, Anna N.; Kirdyasheva, Anna G. (Zootaxa, 2019)
Australia harbors numerous peculiar organisms, but microscopic aquatic invertebrates remain scarcely studied here. Cladocera (Crustacea: Branchiopoda) is considered as one of the most important models for freshwater biogeography, but the lack of adequate species identifications devalues large-scale biogeographical conclusions. In this paper we redescribe morphology of rare and poorly known Moina australiensis Sars, 1896 based on material from its terra typica. Among Australian moinids, M. australiensis is similar to M. tenuicornis Sars, 1896. These two taxa reliably differ from each other in (1) proportions of the antenna I and (2) armature of the inner margin of valve. M. australiensis has a relatively short antenna I and setulae near ventral setae on inner side of the valve grouped into bunches. M. tenuicornis has an elongated antenna I and setulae on described region forming a uniform, continuous row. Presumably, distribution ranges of both species are restricted to Australia. Also, according to literature data, M. baylyi Forró, 1985, M. flexuosa Sars, 1896 and M. propinqua Sars, 1885 may be considered as peculiar Australian taxa. At the same time, M. micrura Kurz, 1875, M. aff. weismanni Ishikawa, 1896 and Moinodaphnia macleayi (King, 1853) have significantly broader distribution ranges. In fact, distribution ranges of all these taxa should be re-evaluated in the future based on careful identification of species in the original samples. In this sense, newly conducted morphological redescriptions of some rare and poorly known taxa are only first steps to evaluation of moinid biodiversity in Australia and in the global scale.